The Impact of Illegal Employment of Foreign Workers in Construction Project: Contractor’s Perspective - Shaiful Mazlan, Shazleen Nabila; Sarpin, Norliana; Omar, Roshartini; Khalid, Zailawati; Ismayatim, Norddin (Research in Management of Technology and Business, 2024)
In today’s globalised world, construction projects frequently depend on workforce diversity, including foreign workers, to satisfy the demands of a business sector. While there are many advantages to hiring foreigners legally, like greater productivity and cross-cultural interaction, the problem of illegal employment has grown to be a major worry. Therefore, the objective of this study is to identify factors that lead contractors to hire foreign workers illegally and to identify negative impacts of illegal recruitment of foreign workers on contractors and construction projects. The scope of research is to concentrate on the factors and negative impacts issues that are faced by contractors and construction projects due to employment of illegal workers. The research method of this study is quantitative method where a questionnaire survey was distributed to respondent which is G7 main contractor registered with Construction Industry Development Board (CIDB) in Johor Bahru. The data was collected from 241 respondents which represents 100% response rate. The data analysis method used was descriptive analysis by using Statistical Package for Social Science (SPSS) software. The study findings might be a wide range of expected outcomes for a study on the problem of illegal foreign worker employment that poses a risk to the contractors and construction projects in the construction industry which is this study can provide further understanding of the key factors that contribute to the illegal hiring of foreign workers in the construction sector. Also, it has the ability to assess how illegal employment affects construction projects as possible negative effects on contractors and the study could determine how well the problem is being addressed by the current legal and regulatory structures. In conclusion, although the employment of illegal foreign workers in construction industry has several negative impacts and factors, there are a range of actions that can be taken to expand the opportunities and space for improvement in order to prevent this from happening in the future.